Problems in the Development of Science - Ainur Awaliah; Maspuroh; Aghna Rahmat; Julfiah Afifah (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
It cannot be denied that the philosophy of science, which is part of the philosophy of knowledge or epistemology, explains the answers to various questions. Philosophy of science is a field of philosophical study that generally investigates the conditions and forms of scientific knowledge. Moreover, the philosophy of science is closely related to logic and methodology. Basically, the philosophy of science aims at full responsibility for a scientist. So an "overview" is needed to lay out a network of interactions to greet each other towards the integral and integrative nature of science. In order to achieve knowledge that is more valid, better and useful continuously and sustainably.